WHEN SHE STOPS WORKING: REFRAMING SOCIAL REPRODUCTIVE LABOUR IN CONTEMPORARY MALAYALAM CINEMA: English - V, Sreebitha P; C. Labeeba (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Building on feminist theories of social reproductive labour, the paper examines the obscured domain of social reproductive labour in contemporary Malayalam cinema. Using Veruthe Oru Bharya (2008), Njandukalude Naattil Oridavela (2017), and The Great Indian Kitchen (2021) as primary texts, the paper demonstrates how these films negate the usual glorification of women’s social reproductive labour as markers of femininity by presenting instances of its disruption through voluntary withdrawal. Veruthe Oru Bharya (2008) portrays how the withdrawal from domestic work of Bindu, a housewife, exposes her highly oppressive patriarchal husband Sugunan to the hitherto invisible labour she performed. In Njandukalude Naatil Oridavela (2017), the intentional temporary withdrawal of Sheela, a working mother, from her domestic role after her cancer diagnosis, compels the household to confront the naturalised double burden borne by working women. The Great Indian Kitchen (2021) presents a powerful depiction of the unpaid gendered labour, culminating in the female protagonists’ walkout. We argue that by interrupting the flow of reproductive labour, these films call for a critical rethinking of the gendered roles underpinning domestic life, while signalling Malayalam cinema’s growing engagement with feminist questions of labour.